The Implementation Of Entek Bungker Customs Before Marriage In Tebo Village An Islamic Law Perspective - Nafisah, Fiddha; Nurul Wathoni, Lalu Muhammad (JATISWARA, 2024)
This study aims to examine the implementation of the Entek Bungker tradition before marriage in the community of Tebo Village, Poto Tano District, West Sumbawa Regency, and assess its compliance with Islamic law principles. This tradition is considered mandatory as a form of physical and spiritual purification for prospective couples, while also believed to ward off misfortune and enhance marital blessings. However, a legal gap arises as this tradition lacks explicit regulation in Islamic law or positive law, leading to debates regarding its legal status. This study employs a qualitative approach through interviews and observations to understand the community’s perception of this tradition. The findings reveal that although the Entek Bungker tradition is rooted in local beliefs and ancestral values, it does not contradict Islamic law as long as it aligns with the principle of monotheism (tawhid). Islamic law permits local traditions as long as they are consistent with Islamic beliefs and do not conflict with established religious principles.